1998
DOI: 10.1149/1.1838835
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered Cobalt‐Carbon‐Nitrogen Thin Films as Oxygen Reduction Electrocatalysts: I. Physical and Electrochemical Characterization

Abstract: Thin films of amorphous Co-C-N mixtures which were co-sputtered in vacuum showed good catalyst properties for oxygen reduction in alkaline solution. The optimal catalytic activity was Co0 48C0 16N0 .The oxygen reduction for these films proceeds via a four-electron pathway and the Co2 /Co3 redox couple is shown to be responsible for the oxygen reduction reaction. The performance is comparable to transition metal macrocycles in alkaline solutions. Evidently, intact structures of the macrocycles are not necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 3 publications
0
31
0
1
Order By: Relevance
“…However, their results were obtained in a neutral solution. Deng et al showed thin films of amorphous Co-C-N mixture which were co-sputtered in vacuum had good catalyst properties for oxygen reduction in alkaline solution [27,28].…”
Section: Transition Metal Nitrides and Carbonitrides As Cathode Catalmentioning
confidence: 99%
“…However, their results were obtained in a neutral solution. Deng et al showed thin films of amorphous Co-C-N mixture which were co-sputtered in vacuum had good catalyst properties for oxygen reduction in alkaline solution [27,28].…”
Section: Transition Metal Nitrides and Carbonitrides As Cathode Catalmentioning
confidence: 99%
“…Some promising nonplatinum electrocatalsysts for ORR have been developed, i.e. precious metal Pd [6][7][8] or Ru-based materials [9][10][11][12][13][14][15][16][17][18][19][20] and nonprecious-metal chalcogenides [21][22][23][24][25][26], carbides [27][28][29][30][31][32][33], nitrides [34][35][36][37][38], macrocycle materials [39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Hence non-noble metal catalysts can also be prepared by using different sources of nitrogen, transition metals and carbon for synthesis at elevated temperature. Different approaches have been reported so far in literature [16][17][18][19]. Ozkan and co-workers used iron-and nickel-impregnated alumina and silica supports to prepare oxygen reduction catalysts by chemical vapor deposition of acetonitrile [18].…”
Section: Introductionmentioning
confidence: 99%
“…Ozkan and co-workers used iron-and nickel-impregnated alumina and silica supports to prepare oxygen reduction catalysts by chemical vapor deposition of acetonitrile [18]. Deng and Dignam previously prepared Co-C-N catalysts by means of vacuum sputter deposition [19]. Recently, Bashyam and Zelenay reported a cobalt-polypyrrole-carbon catalyst which showed good oxygen reduction activity and remarkable stability in PEMFC testing, even without heat-treatment [20].…”
Section: Introductionmentioning
confidence: 99%